Development and characterisation of kenafnanohybrid dental composites - Rasid, Noorasyikin Ab (2024)
Natural fibres such as kenaf fibres have enormous potential in replacing synthetic fibre used for composite reinforcement. This study aimed to optimize the bonding mechanism between kenaf and nanohybrid dental composite from rice husk and investigate mechanical properties of this composite. Kenaf fibres was processed to obtain cellulose nanocrystals (CNC) and silane treated with hybridization of tetraethyl orthosilicate (TEOS) sol gel and γ-Methacryloxypropyltrimethoxysilane (γ- MPS). The treated CNC was investigated through Fourier-transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). Six specimens from each group with different ratio of γ-MPS and TEOS were prepared for compressive and flexural investigation. The experimental composites were compared with commercial nanohybrid composite and fibre reinforced composite (Ever-X posterior, Filtek Z350 and Neofil). Data was statistically analysed using one-way ANOVA test and the fracture surfaces of the samples were subjected to scanning electron microscope (SEM) assessment. FTIR results showed formation of chemical bonds between kenaf CNC with γ-MPS and TEOS sol gel. TGA showed highest decomposition temperature in non-silane treated kenaf fibre compared to silane treated kenaf fibre. Mean flexural and compressive strength between all groups showed statistically significant results (p=0.000). Experimental composite group with fibre reinforced showing higher flexural strength by 31 % while compressive strength increases by 38% compared to non- fibre reinforced composite, however the strength was lower as compared to commercial composites. The compressive strength of all the experimental composites were significantly lower than that of commercial composites. Silane treatment showing evidence of modification and improved bonding between the kenaf fibres and the resin matrix, even though the strength was lower than the commercial composite.